Faktor-faktor yang Mempengaruhi Ibu dalam Memberikan Makanan Tambahan bagi Balita di Desa Rundeng - Salvia, Depi; Rahma, Cukri; Mulyani, Itza; Marniati, Marniati (Polyscopia, 2024)
Providing supplementary food made from local ingredients is an effective way to address nutritional issues among toddlers. In Desa Rundeng, toddlers are underweight due to poor dietary habits, such as frequent consumption of fast food and insufficient intake of fruits, vegetables, milk, and other nutritious foods. Additionally, mothers in the area have limited knowledge about preparing balanced supplementary foods to support toddler growth. This study aims to examine the factors influencing the provision of supplementary food for toddlers in Desa Rundeng. A quantitative descriptive research method was employed, with univariate and bivariate data analysis, conducted in May in Desa Rundeng, Aceh Barat, within the Johan Pahlawan Health Center area. A total of 68 respondents participated in the study. The results indicate that knowledge, attitude, income, and socio-cultural factors significantly affect the provision of supplementary food, as evidenced by a p-value < 0.05. These findings highlight the importance of educating mothers on the nutritional value of supplementary foods to ensure the healthy growth and development of toddlers.